Evaluation of Analgesic Activity of Extracts of Jasminum sessiliflorum - Ruby Philip (Journal of Global Pharma Technology, 2020)
The present study was designed to investigate analgesic activity of ethyl acetate and ethanolic extracts of Jasminum sessiliflorum. The analgesic activity was assessed by using acetic acid induced writhing method and tail immersion tests in rats. The ethyl acetate and ethanolic extracts decreased the acetic acid induced abdominal contractions and also significantly increased the reaction time of tail immersion test [1]. These results showed that the plant extracts had both central and peripheral analgesic action. The results suggest that the extracts of J.sessiliflorum possesses potent analgesic properties, which support its use in traditional medicine and suggesting that the plant should be further investigated for its pharmacological active natural products [2]